Respuesta :
Start by factoring [tex] x^2 - 4x - 5[/tex]. Your two factors will be in the form (x + a) and (x + b). You want two numbers a and b to multiply to -5 and add to -4. Test out various numbers, and you'll find that -5 and 1 work!
That means your factors are (x - 5) and (x + 1). You can double check this by foiling and seeing if you get your original equation.
Since you want to find the zeroes for that equation, that means y = 0. Remember that anything multiplied by 0 is 0, so you can set each of your factors equal to zero and solve for x. The x-values are your zeros:
x - 5 = 0
x = 5
x + 1 = 0
x = -1
-----
Answer: 5 and -1
That means your factors are (x - 5) and (x + 1). You can double check this by foiling and seeing if you get your original equation.
Since you want to find the zeroes for that equation, that means y = 0. Remember that anything multiplied by 0 is 0, so you can set each of your factors equal to zero and solve for x. The x-values are your zeros:
x - 5 = 0
x = 5
x + 1 = 0
x = -1
-----
Answer: 5 and -1
Answer:
x=5 or x=-1
Step-by-step explanation:
The zeroes of the equation is when the x values when y=0.
We can determine this using a method that when we times out the brackets of our simplification we arrive at the original equation. We know that we must get -5 and -4x and x^2:
We can write:
[tex]y=x^2-4*x-5=0[/tex]
[tex](x-5)*(x+1)=0[/tex]
If we use the rules of algebra and multiply each term with each other:
[tex]x*x+x*1-5*x-5*1=0[/tex]
We can simplify:
[tex]x^2-4*x-5=0[/tex]
We end up with the original equation:
Therefore the zeros of the equation is when:
[tex](x-5)*(x+1)=0[/tex]
[tex]x-5=0[/tex] and [tex]x+1=0[/tex]
[tex]x=5[/tex]
[tex]x=-1[/tex[
x=5 or x=-1